In vivo evaluation of Trás-os-Montes natural cosmetic ingredients: Impacts on Drosophila melanogaster longevity and genotoxicity (Research, Society and Development, 2024)
Our body's well-being is intricately linked to external factors, including temperature, humidity, pollution, microorganisms, and the daily food we consume. Nurturing our bodies involves harnessing the benefits of various plants that contribute to the production of diverse cosmetics. Natural elements such as almonds (Prunus dulcis), elderberries (Sambucus nigra), olives (Olea europaea), and grapes (Vitis vinifera) have demonstrated a range of biological activities, holding potential for therapeutic applications. This study aimed to assess the in vivo impact of these natural ingredients on longevity and genotoxicity/antigenotoxicity in Drosophila melanogaster. Longevity was evaluated through regular observations of Drosophila mortality. The somatic mutation and recombination assay were conducted to determine the antigenotoxic potential of the natural ingredients. The findings revealed that these ingredients influenced longevity, and they also exhibited antigenotoxic potential, with elderberry yielding the most promising results. The growing importance of natural and organic cosmetics underscores the significance of identifying ingredients with antigenotoxic effects, offering a promising avenue of research in recent years. Such ingredients could play a crucial role in safeguarding against DNA damage and its subsequent consequences.